Sailing directions for the North-American pilot : Containing the Gulf and River St. Laurence, the whole Island of Newfoundland, including the straits of Bell-Isle, and the coast of Labradore. Giving a particular account of the bays, harbours, rocks, land-marks, depths of water, latitudes, bearings, and distance from place to place; the setting and flowing of the tides, &c. founded on actual surveys, taken by surveyors that have been employed by the admiralty, and other officers in the king's service. Published by permission of the Right Honourable the Lords Commissioners of the Admiralty. (Tufts University. Tisch Library., 2015)
1 online resource .; A made-up volume of separately published items with a general titlepage.; Various paging.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Indexed in: English Short Title Catalog N46758